Patnership Analysis between Jatitujuh Sugar Factory with Sugarcane Factoryin Majalengka,West Java - Fadilah, Ratna; S, Sumardjo (Sodality: Jurnal Sosiologi Pedesaan, 2011)
The aim of this research was to know the implementation of a partnership between sugar mill and sugar cane farmer folk and its relationship to the effectiveness of partnership and community empowerment. This research was conducted in PG Jatitujuh, Majalengka, Province of West Java. Research approach designed by survey, the research respondents were 46 farmer group chairmen. The research uses quantitative and qualitative statistical method with Rank Spearman Correlation to examine variables. Results showed that the partnership helps in empowering the community and increasing the effectiveness of the partnership.